(untitled) (Research, Society and Development, 2021)
In the postoperative period of a dental implant, the patient might experience several inflammation symptoms such as: swelling, pain when chewing, bleeding and secretion formation in the implanted area. In this context, the use of laser in implantology is a procedure that improves the technique of dental implant promoting an effectively implant osseointegration due to its biostimulant potential stimulating healing. The objective of this work was to carry out an integrative review of the current literature about the use of laser in implantology, highlighting the benefits, limitations, challenges, and its relevancy and impact on oral health and society. How the application of laser supports the process of osseointegration in implantology? An integrative review had been done through scientific articles in the databases PubMed, Lilacs e Scopus, using the descriptors “dental implant”, “low level laser therapy” and “osseointegration”, indexed from 2016 to 2020 which dealt with clinical trial, review, systematic review, meta-analysis and randomized controlled. There were excluded articles from books, documents, conference paper, book chapters and editorials. After the eligibility criteria there were analyzed 15 articles mainly published in English. The studies have shown that the application of a low level laser helps implant dentistry regarding the osseointegration of the implant, decreasing the postoperative period, pain and risk of infection due to its biostimulant potential, analgesic and anti-inflammatory. This effectiveness stems from an increase in epithelial and fibroblast proliferation, a stimulus of collagen synthesis, phagocytic activity and endorphin induction. Nevertheless, there are not yet enough case studies, especially in human beings to provoke, indeed the application of laser during the bone-implant integration process, which is called osseointegration. However, it is notable that this technique shows to be promissory in the dentistry industry.